One wrong move - Pettrey, Dani (Jeopardy falls, 2024)
"Making amends for his criminal past, Christian Macleod has become one of the country's top security experts. But a string of heists brings attention from Andi Forster, an insurance investigator with her own checkered past. The two of them are drawn into a dangerous game with an opponent bent on revenge, and one wrong move could be the death of them both"--